Low magnetisation alloys for in-plane spin transfer torque devices - (:unkn) unknown (AMER INST PHYSICS, 2012)
Magnetic properties of thin films of three in-plane alloy systems, namely, Co40Ni40-xCrxB20, Co40Fe40-xNixB20, and Co40Fe40-xCrxB20 are investigated with a view to reducing the critical current density (j(c)) for spin transfer torque switching in MgO barrier magnetic tunnel junction nanopillars. In all three systems, the saturation magnetisation, M-s, decreases with increasing Cr or Ni substitution. The Co40Fe40-xCrxB20 alloy system is found to be the best in terms of reducing Ms, while maintaining a high tunnel magnetoresistance ratio. Ferromagnetic resonance experiments revealed that the damping coefficient of CoFeCrB alloy remains unchanged with increasing Cr content, but jc is reduced by a factor of four to 4.9 x 10(5) A/cm(2) by using a Co40Fe32.7Cr7.3B20 free layer while maintaining a magnetoresistance of around 60 %. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4723824]
Keywords: MULTILAYER; EXCITATION